Embracing ambiguity: agile insights for sustainability in engineering in traditional higher education and in technical and vocational education and training - Towey, Dave; Walker, James; Ng, Ricky (Emerald, 2019)
Embracing reflective practice and retrospection, with a goal of identifying commonalities, this paper examines delivery of engineering subjects in both traditional higher education (THE) and technical and vocational education and training (TVET). Reflections on actions and autoethnography were employed to examine the teaching and learning experiences of three educators across two higher education (HE) institutions (HEIs), in the greater Chinese context. Literature reviews and historical contexts are outlined to support the approaches and insights identified. The paper presents a number of common characteristics and challenges identified across both THE and TVET. Drawing on the successful embrace of ambiguity and change in recent software engineering (SE) development paradigms, recommendations are then made for how the agile SE themes can be applied in a larger sense to address the wider challenges facing both THE and TVET. To the best of our knowledge, this is the first time engineering education has been examined and contrasted in the contexts of THE and TVET. The similarities and common challenges may represent a new focus for related work, and the presented insights, from agile methodologies in software engineering, represent a new perspective for viewing future HE and TVET sustainability.